Addition of erlotinib to fluoropyrimidine-oxaliplatin-based chemotherapy with or without bevacizumab: Two sequential phase I trials - CARLOMAGNO, CHIARA (D.A. Spandidos, 2011)
The combination of EGFR inhibitors and anti-angiogenic drugs has a strong pre-clinical rationale, yet its use has produced controversial clinical results. We conducted two sequential phase I trials to evaluate the feasibility and the recommended dose of erlotinib when combined with fluoropyrimidine-oxaliplatin-based chemotherapy with or without bevacizumab. A total of 21 metastatic colorectal cancer (mCRC) patients were treated in two sequential phase I trials. In the first trial, 12 patients were treated with escalating doses of erlotinib plus FOLFOX. In the second, 9 patients were treated with escalating doses of erlotinib combined with oxaliplatin, capecitabine and bevacizumab. No MTD was reached in either of the trials. The only dose-limiting toxicities observed were neutropenia and diarrhea. No unexpected toxicities were noted. Hematological toxicity was the most frequently noted adverse event with infusional 5FU therapy, while gastrointestinal toxicity was the most common adverse event. In the second trial most patients withdrew from treatment due to toxicity, and less than half completed the therapeutic program as per protocol, mostly due to toxicity. In conclusion, the present study confirms the disappointing results of the double combination of EGFR inhibitors and anti-angiogenic drugs in mCRC patients.